1973
DOI: 10.1002/j.1556-6978.1973.tb01553.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prepracticum Laboratory Training Experience

Abstract: This article reviews the literature pertinent to prepracticum laboratory experiences in counselor education and describes the elements and the evaluation of one such program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Even more importantly, the many statistically significant results in IDET studies may obscure the fact that even after the most lengthy and successful IDET program with graduate counselor trainees (e.g., Carkhuff et al, 1968;Carkhuff & Truax, 1965;Emener, 1973), the average facilitativeness level communicated by trainees was less than (or just barely equal to) the level that has been empirically established as the minimum necessary to create a truly therapeutic milieu (i.e., 5 on a 9-point scale, 3 on a 5-point scale; Mitchell, Bozarth, & Krauft, 1978). With shorter IDET programs and paraprofessional trainees (e.g., Brockhaus et al, 1973;Dooley, 1975;VanderKolk, 1973), even the most successful trainees almost never even approached the minimal facilitativeness level!…”
Section: Integratedmentioning
confidence: 93%
See 2 more Smart Citations
“…Even more importantly, the many statistically significant results in IDET studies may obscure the fact that even after the most lengthy and successful IDET program with graduate counselor trainees (e.g., Carkhuff et al, 1968;Carkhuff & Truax, 1965;Emener, 1973), the average facilitativeness level communicated by trainees was less than (or just barely equal to) the level that has been empirically established as the minimum necessary to create a truly therapeutic milieu (i.e., 5 on a 9-point scale, 3 on a 5-point scale; Mitchell, Bozarth, & Krauft, 1978). With shorter IDET programs and paraprofessional trainees (e.g., Brockhaus et al, 1973;Dooley, 1975;VanderKolk, 1973), even the most successful trainees almost never even approached the minimal facilitativeness level!…”
Section: Integratedmentioning
confidence: 93%
“…Blocksma and Porter (1947), Carkhuff and Truax (1965), and later Burck, Jacobs, Sauber, Stone, and Thomson (1973), Delaney, Long, Masucci, and Moses (1969), Emener (1973), and Redfering (1973) have demonstrated that IDET generates significant increases in trainees' abilities to communicate FC to clients. Several investigations have shown that between 1 and 100 hours of IDET is significantly more effective than no training (Ashworth, 1971;Berenson et al, 1966;Brockhaus, Marshall, & Dustin, 1973;Butler & Hansen, 1973;Dooley, 1975;Pacoe, Naar, Guyett, & Wells, 1976;Selfridge et al, 1975;Shapiro & Gust, 1974), placebo-control didactic lectures (Gormally et al, 1975;Martin & Carkhuff, 1968), an equivalent amount of "traditional" clinical or counseling training (Carkhuff, Kratchovil, & Friel, 1968;Leitner, 1973;Rye, 1970;VanderKolk, 1973), or an equivalent amount of "experiential" training (Berenson et al, 1966;Rye, 1970).…”
Section: Integratedmentioning
confidence: 97%
See 1 more Smart Citation
“…Various approaches can be used in training laboratories, but most of the experiential exercises involve simulations of counseling settings. In a model proposed by Emener (1973), later stages of the prepracticum experience include extended interactions with persons from outside the class. Therefore, real clients may be solicited for this training experience.…”
Section: Clients Used In Trainingmentioning
confidence: 99%
“…A variety of appropriate techniques (at the discretion of the trainers) were used during all three stages of training, including role playing and audio and video playback and interviewing to facilitate learning within the training process (consult Carkhuff 1969;Emener 1973). The trainers were 30 and 32 years old, held doc-toral degrees in counseling, and had individually conducted over 1,000 hours of communications and human relations training in a variety of educational, institutional, and industrial settings.…”
Section: Training Processmentioning
confidence: 99%